IMPLEMENTASI MODEL DISCOVERY LEARNING MENGGUNAKAN LESSON STUDY UNTUK MENINGKATKAN HASIL BELAJAR SISWA - Wijaya, Adinda Silvy; Wahyu Mulyani, (Jurnal Penelitian Pendidikan Indonesia (JPPI), 2025)
The learning process in the modern era requires teachers to not only transfer knowledge, but also develop 21st century skills in students, such as communication and collaboration. The implementation of Discovery Learning combined with Lesson Study has great potential in improving students' communication and collaboration skills. This study focuses on the implementation of the Discovery Learning model with the Lesson Study approach as an effort to improve student learning outcomes. With this approach, learning is expected to be more effective, interactive, and relevant to the demands of the times. The research method used is classroom action research (CAR) based on lesson study. The subjects of this study were grade VI students of UPT SDN Kingking 1 Tuban. Data collection techniques used observation and tests. The results of the study were obtained in cycle 1, the number of students was 24 with an average score of 73.8 and 16 students completed. In cycle 2, the number of students was 24 with an average score of 86.25 and 19 students completed. While in cycle 3, the number of students was 24 with an average score of 100 and 24 students completed.